2015
DOI: 10.3857/roj.2015.33.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of adjuvant radiation therapy and prognostic factors in early stage uterine cervical cancer

Abstract: PurposeTo evaluate the outcomes of adjuvant radiotherapy (RT) and to analyze prognostic factors of survival in the International Federation of Gynecology and Obstetrics (FIGO) IB-IIA uterine cervical cancer.Materials and MethodsWe retrospectively reviewed the medical records of 148 patients with FIGO IB-IIA uterine cervical cancer who underwent surgery followed by adjuvant RT at the Yonsei Cancer Center between June 1997 and December 2011. Adjuvant radiotherapy was delivered to the whole pelvis or an extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…ADC in cervix cancer has been considered to have biological aggressiveness and to be more resistant to adjuvant treatment [ 25 , 26 ]. In the present study, ADC histology carried a poor prognosis with 71.8% of DMFS and 61.8% of DFS at 5 years compared to SqCC with 87.7% of DMFS and 84.1% of DFS at 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ADC in cervix cancer has been considered to have biological aggressiveness and to be more resistant to adjuvant treatment [ 25 , 26 ]. In the present study, ADC histology carried a poor prognosis with 71.8% of DMFS and 61.8% of DFS at 5 years compared to SqCC with 87.7% of DMFS and 84.1% of DFS at 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The size and histological type of tumor were reported to be associated with poor OS and disease free survival in cervical cancer. 30,31 Grigsby et al 32 enrolled 1239 cervical cancer patients and demonstrated the survival rates of squamous cell carcinoma patients were similar to those of adenocarcinoma. Bradley et al retrospectively reviewed data from 335 women in stage II to IV who received weekly cisplatin and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the lymph node positivity is one of the most prominent prognostic factors for recurrence and death in patients with cervical cancer ( 15 , 16 ). Conversely, other studies reported conflicting results that positive pelvic lymph nodes (PLNs) do not affect recurrence and survival ( 17 , 18 ). A GOG study about early-stage cervical cancer undergoing surgery showed significantly worse disease free interval between patients with positive pelvic lymph nodes but not survival ( 19 ).…”
Section: Introductionmentioning
confidence: 99%